Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T16:47:59+01:00
A 5a + 3 dla a= -2
-10+3=7
b 7x -2y dla x = 3 i y = 5
21-10=11
c a² + b² dla a = 8 i b = 6
64+36=100
d (4x - 2y) : 2 dla x = 5 i y = 3
(20-6):2= 14:2=7
e 8x² - 2 dla x = ½
8* 1/4 -2 = 2-2 = 0
f x + 2y -1 dla x = -3 i y = 4,5
-3+9-1=5
2 3 2
2010-02-20T16:49:36+01:00
A 5a + 3 dla a= -2 czyli -10+3=-7
b 7x -2y dla x = 3 i y = 5 czyli 21-10=11
c a² + b² dla a = 8 i b = 6 czyli 16+12=28
d (4x - 2y) : 2 dla x = 5 i y = 3 czyli (20-6):2=14:2=7
e 8x² - 2 dla x = ½ czyli 8-2=6
f x + 2y -1 dla x = -3 i y = 4,5 czyli -3+9-1=6-1=5
2 3 2
2010-02-20T16:51:23+01:00
A) a=-2
5a+3=5*(-2)+3=-10+3=-7
b) x=3
y=5
7x-2y=7*3-2*5=21-10=11
c) a=8
b=6
a²+b²=8²+6²=64+36=100
d)x=5
y=3
(4x-2y):2=(4*5-2*3):2=(20-6):2=14:2=7
e) x=½
8x²-2=8*(½)²-2=8*¼-2=2-2=0
f) x=-3
y=4,5
x+2y-1=-3+2*4,5-1=-3+9-1=5
1 1 1